INDOOR AIR QUALITY FUELLING INDIA’S COVID-19 INFECTION - KUMAR, SURAJ; JHA, AJAY NATH (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Just as the smell gets diluted by ventilation, the dangerous concentration of the virus can also get reduced by ensuring appropriate amount of outdoor air flows in. In closed and stale space droplets and aerosol gets quickly concentrated and greatly increases the risk of transmission of virus in that area. Visit to any nearby shopping malls, newly furnished coaching classes, modern residential buildings, government offices, hotels, restaurants and even hospitals shows that they are nothing but an assortment of closed and unventilated spaces. These closed space acts as Super spreader of the virus. Peak test positive rate of 22.6% per hundred test is observed during the month of May, which is a result of high humidity particulate matter concentration temperature CO2 concentration.